Linear Matrix Inequality Based Synthesis of PI Controllers for PMSM with Uncertain Parameters - Koch, Gustavo G.; Gabbi, Thieli S.; Vieira, Rodrigo P.; Pinheiro, Humberto; Bernardes, Thiago A.; Oliveira, Ricardo C. L. F.; Montagner, Vinícius F. (Eletrônica de Potência, 2018)
This paper addresses the design of robust PI controllers for permanent magnet synchronous motors in terms of a linear matrix inequality based problem. A polytopic model of the plant is obtained and validated for the motor uncertain parameters belonging to intervals. The design procedure proposed here encompasses: i. suitable plant uncertainties inclusion and the use of practical design control constraints; ii. robust PI computation based on linear matrix inequalities with a very fast solution; iii. simulation analyses; and iv. experimental evaluations. The robust PI controller can produce superior speed regulation than a PI controller designed only for the nominal parameters, including better disturbance rejection and H-infinity performance. Experimental results confirm the viability of the proposal, which can be seen as an efficient alternative to trade off performance and robustness for PI controllers in this application.